Corporate Sustainability Performance Measurement Systems: A Review and Research Agenda - Searcy, Cory (2012)
Corporate sustainability performance measurement systems (SPMS) have been the subject of a growing amount of research. However, there are many challenges and opportunities associated with the design, implementation, use, and evolution of these systems that have yet to be addressed. The purpose of this article is to identify future directions for research in the design, implementation, use, and evolution of corporate SPMS. A concise review of key literature published between 2000 and 2010 is presented. The literature review focuses on research conducted at the both the individual corporation- and sector-levels. The review of published literature provides a basis for the identification of a structured set of 65 key research questions to guide future work. The research questions will be of interest to both practitioners and researchers in corporate sustainability performance measurement.
Keywords: Corporate Sustainability; Metrics; Performance measures; Composite indicators; Indicators; Sustainable Development